The development of research competence among specialist registrars in South Africa: Challenges and opportunities for research education and capacity development - K Moxley (South African Medical Association, 2022)
To equip physicians with the competencies that support evidence-based healthcare, curriculum frameworks for medical education often promote scholarly activity as an essential component of training. Many medical schools worldwide expect medical trainees to participate in some form of research during their undergraduate and postgraduate training. This requirement is especially important in Africa, where there is also much need to develop clinical research capacity and an evidence base that is contextualised to the specific healthcare challenges on the continent. In South Africa, the requirement for specialist trainees to complete a research project (as part of a Master of Medicine, MMed) was made mandatory from 2011 and has introduced several difficulties for many training centres. There is concern that institutions are failing to develop medical specialists who are competent in their role as scholars, particularly in their ability to conduct research. In this article, I review the South African literature that discusses the research component of medical specialist registration. In addition to summarising the challenges associated with MMed projects and recent efforts to address them, I interrogate whether the current status of MMed research education is likely to be contributing to the successful development of research competence among this unique group of postgraduates. By consolidating the current debate, I hope to encourage a point of departure between criticising the challenges and adopting proactive strategies to address them. There is a great need for medical educators to design innovative and learner-centred research education strategies that can better develop research competence among African healthcare professionals.